The Valuation of Interest Rate Derivatives: Empirical Evidence from the Spanish Market - Juan M. Moraleda; Ton Vorst (Tinbergen Institute, 1996)
This paper studies empirical issues of one-factor yield curve models. We focus on the models by Hoand Lee (1986), Hull and White (1990) and Moraleda and Vorst (1996). To be consistent in thecomparison of the models, we derive them all within the Ritkchen and Sankarasubramanian (1995)framework, which is a subset of the very general Heath, Jarrow and Morton (1992) model. Weestimate model parameters from historical time series of government bond prices. The model byMoraleda and Vorst (1996) turns out to best explain the yield curve dynamics through time.Moreover, humped shapes in the volatility structure as modelled in this model are typically found.Next, we use these parameter estimations for pricing options traded in the Spanish financial market.A comparison between model and market option prices is provided.
Keywords: 330; Zinsderivat; Theorie; Spanien